Cholesterol-PEG comodified poly (N-butyl) cyanoacrylate nanoparticles for brain delivery: in vitro and in vivo evaluations - Xiao Hu; Feifei Yang; Yonghong Liao; Lin Li; Lan Zhang (Taylor & Francis Group, 2017)
This study investigated cholesterol-polyethylene glycol (PEG) comodified poly (ethyleneglycol)-poly (lactide) nanoparticles (CLS-PEG NPs) as a novel, biodegradable brain drug delivery system and included an evaluation of its in vitro and in vivo properties. To this end, coumarin-6 (C6), a fluorescent probe, was encapsulated into CLS-PEG NPs by an emulsion polymerization method. We reported that the use of CLS-PEG NPs led to a sustained drug release in vitro. Additionally, cell viability experiments confirmed their safety. The uptake and transport of CLS-PEG NPs, by bEnd.3 cells (an immortalized mouse brain endothelial cell line), was significantly higher than that of a control C6 solution. An investigation of the uptake mechanisms of different NP formulations demonstrated that cholesterol modifications may be the primary way to improve the efficiency of cellular uptake, wherein macropinocytosis may be the most important endocytic pathway in this process. An investigation of the transport mechanisms of CLS-PEG NPs also implicated macropinocytosis, energy and cholesterol in bEnd.3 cells lines. Following an intravenous (IV) administration to rats, pharmacokinetic experiments indicated that C6-loaded CLS-PEG NPs achieved sustained release for up to 12 h. In addition, IV delivery of CLS-PEG NPs appeared to significantly improve the ability of C6 to pass through the blood-brain barrier: the concentration of C6 found in the brain increased nearly 14.2-fold when C6 CLS-PEG NPs were used rather than a C6 solution. These in vitro and in vivo results strongly suggest that CLS-PEG NPs are a promising drug delivery system for targeting the brain, with low toxicity.